2011
DOI: 10.1105/tpc.111.085183
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Membrane Binding of the Intrinsically Disordered Dehydrin Lti30, a Cold-Induced Plant Stress Protein

Abstract: Dehydrins are intrinsically disordered plant proteins whose expression is upregulated under conditions of desiccation and cold stress. Their molecular function in ensuring plant survival is not yet known, but several studies suggest their involvement in membrane stabilization. The dehydrins are characterized by a broad repertoire of conserved and repetitive sequences, out of which the archetypical K-segment has been implicated in membrane binding. To elucidate the molecular mechanism of these K-segments, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
193
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(200 citation statements)
references
References 57 publications
(81 reference statements)
7
193
0
Order By: Relevance
“…For example, dehydrin Lti30 (for LOW TEMPERATURE-INDUCED 30) functions in cold tolerance by lowering the temperature of the lipid phase transition, and the membrane-Lti30 interaction is regulated by the pH-dependent His switch and phosphorylation of the disordered dehydrin (Eriksson et al, 2011). Disordered structures of LEA proteins impart the ability to sequester water and sugars in a tight hydrogen-bonded network to form stable hydrated gels.…”
Section: Lea Protein Function In Response To Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dehydrin Lti30 (for LOW TEMPERATURE-INDUCED 30) functions in cold tolerance by lowering the temperature of the lipid phase transition, and the membrane-Lti30 interaction is regulated by the pH-dependent His switch and phosphorylation of the disordered dehydrin (Eriksson et al, 2011). Disordered structures of LEA proteins impart the ability to sequester water and sugars in a tight hydrogen-bonded network to form stable hydrated gels.…”
Section: Lea Protein Function In Response To Abiotic Stressmentioning
confidence: 99%
“…Among LEA proteins, phosphorylation-regulated ion binding is exhibited by the acidic group 2b LEA dehydrins (Alsheikh et al, 2005); phosphorylation modulates the binding-induced folding of Thellungiella salsuginea DEHYDRIN-1 (DHN-1) and DHN-2 associated with membranes (Rahman et al, 2011a) and the membrane binding of Arabidopsis thaliana dehydrin Lti30 (Eriksson et al, 2011); and phosphorylation of the maize (Zea mays) LEA protein Rab17 regulates its cellular localization in that unphosphorylated Rab17 is retained in the nucleolus, whereas phosphorylated Rab17 is mainly cytoplasmic (Riera et al, 2004). Phosphorylation in the disordered N-terminal domain of bZIP protein HY5 (for LONG HYPOCOTYL 5) by a lightregulated kinase activity affects its stability and activity in Arabidopsis (Hardtke et al, 2000).…”
Section: Intrinsic Disorder Facilitates Phosphorylationmentioning
confidence: 99%
“…Deletion studies with the maize dehydrin ZmDHN1 showed that the K segments are likely responsible for binding to these different membranes, although which residues were responsible was not determined, nor if there is a weaker interaction with the segment (28). A need to closely examine the role of the segment is driven by a study of the Arabidopsis dehydrin Lti30, which is able to bind liposomes, whereas the K peptide (that is, a peptide consisting of only the 15-residue K segment) failed to bind (32).…”
mentioning
confidence: 99%
“…No effect was observed, but this may not be surprising because this probe partitions in the acyl chain region of the liposome, whereas the polar dehydrins are likely to interact at the liposome surface. The study using Arabidopsis Lti30 dehydrin also examined membrane fluidity by measuring the phase transition temperature of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC):1,2-dimyristoyl-sn-glycero-3-phospho-L-serine liposomes (32). The protein was able to lower the transition temperature of the liposomes, which would allow the plant to maintain membrane fluidity at lower temperatures (32).…”
mentioning
confidence: 99%
“…Dehydrins have been associated with improved freezing tolerance in many species including spinach (Kaye et al, 1998), strawberry (Houde et al, 2004), cucumber (Yin et al, 2006), peach (Wisniewski et al, 1999), birch (Puhakainen et al, 2004), and spruce (Kjellsen et al, 2013). In angiosperms, a characteristic Lys-rich dehydrin motif known as the K-segment interacts with lipids to facilitate membrane binding (Koag et al, 2003;Eriksson et al, 2011). Several in vitro studies have demonstrated dehydrin functions including prevention of aggregation and unfolding of enzymes (using Vitis riparia; Hughes and Graether, 2011), radical scavenging (using Citrus unshiu; Hara et al, 2004), and suppression of ice crystal formation (using Prunus persica; Wisniewski et al, 1999).…”
mentioning
confidence: 99%